Peningkatan Mutu Pendidikan Tinggi Keagamaan Islam Swasta (PTKIS) Melalui Pelayanan Akademik (Telaah Layanan Akademik Di STAIH Pare Kediri) - Harun Umar (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2016)
This paper aims to examine the improvement of the quality of education of PTKIS through academic services. Academic services can be interpreted as an effort made by universities to provide convenience to meet the needs of students related to academic activities. Academic service system consists of at least: academic system, administration system, and information system. The quality of academic services is based on the performance of faculty and administrative staff. The results of this paper show that managing an educational institution required a quality academic service system, which is able to satisfy service users (students). This research method is qualitative with the study of literature that examines theories that exist in the library, the theory is related to the improvement of the quality of College and academic services. The results of this study indicate that the academic service at STAI Hasanudddin Pare is still low under the expected service, but in general academic service standard minimum set. The results of this study are used to improve the factors that can improve the quality of education at STAI Hasanuddin Pare Kediri